2008
DOI: 10.1177/1748895808092428
|View full text |Cite
|
Sign up to set email alerts
|

The 2003 Licensing Act's impact on crime and disorder

Abstract: The Licensing Act 2003, coming into force in November 2005 in England and Wales, abolished set licensing hours for pubs and clubs. The aim was to liberalize a rigid system while reducing the problems of drinking and disorder associated with a standard closing time. This article summarizes the results of an evaluation funded by the Home Office. Despite widespread concern that the legislation would lead to '24-hour drinking' and an increase in associated problems, the experience of the first year shows very litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…Similarly, late night public drinking represents a time of great risk [86,88,95]. Longer licensing hours would be expected to increase the risk of late-night violence and resultant homicide, and restricted licensing to reduce the opportunity for such risk [149][150][151]. It could, of course, be argued to the contrary that longer licensing hours might encourage more sensible drinking patterns, rather than heavy consumption in short periods.…”
Section: Reducing Homicide Ratesmentioning
confidence: 91%
“…Similarly, late night public drinking represents a time of great risk [86,88,95]. Longer licensing hours would be expected to increase the risk of late-night violence and resultant homicide, and restricted licensing to reduce the opportunity for such risk [149][150][151]. It could, of course, be argued to the contrary that longer licensing hours might encourage more sensible drinking patterns, rather than heavy consumption in short periods.…”
Section: Reducing Homicide Ratesmentioning
confidence: 91%
“…Models in which the proposed mechanism for the outlet density impact does not necessarily require high alcohol consumption (eg, where violence occurs due to collisions between drinkers exiting several densely situated on-trade outlets) are relevant for explaining acute harms [23]. …”
Section: Introductionmentioning
confidence: 99%
“…While the Home Affairs Committee reported a 'strong perception among police forces that alcohol-related violence is on the increase' (Home Affairs Select Committee, 2008, p. 36), other studies pointed to a flatlining, or even a small decline, in alcohol-related crime (Babb, 2007;Hough et al, 2008), though these figures may mask significant differences between urban and rural areas (Roberts and Eldridge, 2007;Hadfield and Measham, 2010;Humphreys and Eisner, 2010). Some studies showed little change in admissions to alcohol and emergency departments (Durnford et al, 2008;Hough et al, 2008), while other data suggested a dramatic increase in overall hospital admissions for alcohol-related conditions (HC Deb 21 April 2009 vol 491 c572w). While police support for the Act fell away in (White, 2005, subsequent reviews found police support for many of the new powers -especially the powers to trigger licence reviews and impose Drink Banning Orders (Herring et al, 2008, p. 261;Hadfield et al, 2009, p. 472).…”
Section: -2008: a New Focus On Healthmentioning
confidence: 99%